Peningkatan Kapasitas Kader dalam PenangananPenyakitTuberkulosis - Darlis, Idhar; Rusnita, Rusnita (Window of Community Dedication Journal, 2023)
Mycobacterium tuberculosis bacteria cause TB, which attacks the lungs and other organs. One of the countries with the highest level is Indonesia. The 2022 Global TB Report reports that the TB incidence in Indonesia in 2021 was 969,000 cases, ranking second highest, up 17% from 2020. To find and accompany people with TB, increasing cadre capacity is very important. The involvement of cadres in TB control programs produces efforts that are community-based and for the community. This activity uses lectures and discussions. The total number of activity participants was 45 cadres. Capacity building activities were carried out in Enrekang Regency. The results show an increase in cadres' knowledge, attitudes and actions regarding how to deal with tuberculosis, starting from case discovery, case care, to contact investigation. It is hoped that cadres who have received this capacity increase can disseminate information to the public.